Role of Family Milieu in Tobacco Addiction: A Study in a Tertiary-care Institution in India - Dwivedi, Shridhar; Aggarwal, Amitesh; Singh, Nishant; Aggarwal, Sourabh; Sharma, Vishal (Journal of Health, Population and Nutrition, 2013)
Use of tobacco is singularly responsible for most cases of cancer and coronary artery disease (CAD). Efforts to stop tobacco-use need to be guided by social circumstances. It is believed that family milieu may play a role in tobacco addiction. We studied the prevalence and pattern of tobacco-use in families of 50 consecutive tobacco-user patients who presented to a tobacco-cessation clinic and compared with age- and gendermatched controls (non-users of tobacco). The tobacco-use rates were significantly higher in the family of patients with tobacco-use compared to the control group. We conclude that problems of tobacco-use are not related to individual phenomenon, and efforts for control of tobacco addiction must be focused on entire family. J HEALTH POPUL NUTR 2013 Mar;31(1):130-132 DOI: http://dx.doi.org/10.3329/jhpn.v31i1.14757